IMPROVING THE TENTH GRADE STUDENTS` READING COMPREHENSION ACHIEVEMENT OF NARRATIVE TEXT AND THEIR READING HABIT AT SMA NEGERI 6 OKU BY USING STORY GRAMMAR - Yentri Anggeraini (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACTThe objectives of this study were to find out (1) whether there was significant difference in reading comprehension achievement of narrative text between the tenth grade students of SMA Negeri 6 OKU who were taught by using story grammar strategy and that of those who were not, (2) whether there was significant difference in reading habit between the tenth grade students of SMA Negeri 6 OKU who were taught by using story grammar strategy and that of those who were not. The population of the study consisted of four classes of the tenth grade students of SMA Negeri 6 OKU with the total was 123 which divided equally in experimental and control groups by using cluster random sampling to get the two classes as the sample. At the end of the study the writer found out that there was significant difference in students` reading comprehension achievement of narrative text and their reading habit between the students who were taught by using story grammar strategy and that of those who were not. It was identified that sig. (2-tailed) or p value (0.00) was less than alpha value (0.05) and the independent sample test shows the comparison of reading habit posttest of both experimental group and control group displayed the difference between scores. It was identified that sig. (2-tailed) or p value (0.00) was less than alpha value (0.05) Keywords: Story grammar strategy, reading comprehension, narrative text, reading habit